Force Adaptation Algorithm for Finger Exercise Using Kuka Youbot - Abdul Jalil, Muhammad; Miskon, Muhammad Fahmi; Bahar, Mohd Bazli; Jamaluddin, Muhammad Herman; Ali, Fariz; Yunus, Yusaimi (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
The comfort and safety is still a major impact in designing a rehabilitation robot. This paper presents an adaptive control strategy algorithm for rehabilitation robot using KUKA Youbot for human finger. The algorithm is designed to handle the safety and comfort criteria during finger rehabilitation using finger force feedback. Two algorithms are developed to handle two different types of exercises for patient’s finger. These algorithms are tested in VREP simulation software. The spring damper system is used to simulate the human’s finger along with finger’s mechanical properties. Both algorithms used forced feedback to adapt the limitation of a patient’s finger. The 5 Nm was set as a safety threshold force that human can handle. The result shows that the algorithm has an ability to follow the safety criteria and can adapt the limitation of a human finger.